Formation of Iron (III) Trimesate Xerogel by Ultrasonic Irradiation. Issue 15 (6th April 2022) - Ennas, Guido; Gedanken, Aharon; Mannias, Giada; Kumar, Vijay B.; Scano, Alessandra; Porat, Ze'ev; Pilloni, Martina
Abstract: Fe−BTC materials have attracted vast attention owing to their high chemical stability, adaptable synthesis, and potential applications. Herein, we describe, for the first time, the preparation of iron trimesate gels by ultrasonic (US) irradiation of an aqueous solution of Iron (III) nitrate and trimesic acid. Two different procedures were used: (1) sonication for 10 or 20 minutes, (2) 3 minutes sonication under controlled pH (pH 3–5). After drying, stable Fe−BTC xerogels were obtained from both procedures. The xerogels consisted of interconnected spherical nanoparticles with similar microstructure when analyzed by FT‐IR and PXRD and similar thermal behavior under oxygen in the range of 25–900 °C. When analyzed by Nitrogen adsorption‐desorption at 77 K, all samples showed a permanent porosity with a narrow micropore distribution below 10 Å. Different textural properties were found among samples obtained with the same procedure. The product of 10 minutes sonication had a specific surface area (SSA) of 1042 m 2 /g. Abstract : Water solutions containing the metal salt and the organic linker were processed at different times with ultrasonic irradiation using two different sets of apparatus. The irradiation promoted the formation of Fe−BTC gels that resulted in stable xerogels after the drying process. The xerogels consisted of interconnected nanoparticles with a permanent microporous structure.